Alternatif Lokasi Perumahan oleh Pengembang untuk Masyarakat Berpenghasilan Rendah di Sekitar Kawasan Industri Ngaliyan - Adiyanti Annisa Istikhomah; Asnawi Manaf (Teknik PWK (Perencanaan Wilayah Kota), 2016)
As the main city in the province of Central Java, Semarang under pressure due to population growth is increasing very rapidly. Rapid population growth can lead to the development of the city. Based on research that has been done, the tendency today is the housing development of small-scale housing development undertaken by the developer thus causing inefficiency of land use and waste of public services (Apriani, 2015). The emergence of small-scale housing development undertaken by developers led to urban sprawl. Unfortunately the construction is striking among the people, especially low-income people. This if allowed to continue would be a complex problem, especially on the issue of spatial planning. Ngaliyan district is a district that has an industrial area, so that with the urbanization due to an industrial area and coupled with the rapid population growth, it could trigger an increased demand for high occupancy. Based on this, it is necessary to research related to the procurement of the house footprint for low-income communities are integrated. The purpose of this study is to formulate procurement sole houses for low-income communities in an effort to overcome urban sprawl in District Ngaliyan. The method used in this study is the survey method. The collection of data used in this study is the collection of primary data in the form of observations and interviews, as well as secondary data collection study document. The end result of this study is selected locations procurement sole houses for low income people in the village Boja.